2014
DOI: 10.11564/28-0-561
|View full text |Cite
|
Sign up to set email alerts
|

Mother to daughter transmission of Female Genital Cutting in Egypt, Burkina Faso and Senegal

Abstract: The aim of article is to assess the determinants of mothers to daughters transmission of female genital cutting (FGC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 25 publications
4
31
0
1
Order By: Relevance
“…If this kind of selection occurs, those who emigrate will not have the same attitudes regarding cutting as those who do not. Farina and Ortensi (2014) , for example, surveyed immigrants from practicing countries in Italy and concluded that ignoring selective migration can lead one to overestimate the prevalence and risk of cutting in immigrant populations. Second, in addition to selection, immigrants in Europe and North America might have attitudes about cutting that differ from countries of origin because immigrants change their attitudes after arriving in their new country ( Farina and Ortensi, 2014 , Johnsdotter et al, 2009 ).…”
Section: Effects Of Selection and Acculturationmentioning
confidence: 99%
See 1 more Smart Citation
“…If this kind of selection occurs, those who emigrate will not have the same attitudes regarding cutting as those who do not. Farina and Ortensi (2014) , for example, surveyed immigrants from practicing countries in Italy and concluded that ignoring selective migration can lead one to overestimate the prevalence and risk of cutting in immigrant populations. Second, in addition to selection, immigrants in Europe and North America might have attitudes about cutting that differ from countries of origin because immigrants change their attitudes after arriving in their new country ( Farina and Ortensi, 2014 , Johnsdotter et al, 2009 ).…”
Section: Effects Of Selection and Acculturationmentioning
confidence: 99%
“… Farina and Ortensi (2014) , for example, surveyed immigrants from practicing countries in Italy and concluded that ignoring selective migration can lead one to overestimate the prevalence and risk of cutting in immigrant populations. Second, in addition to selection, immigrants in Europe and North America might have attitudes about cutting that differ from countries of origin because immigrants change their attitudes after arriving in their new country ( Farina and Ortensi, 2014 , Johnsdotter et al, 2009 ). Some might become more negative about cutting as they integrate in a non-cutting society, while others might become more positive about cutting as a way to maintain and assert cultural ties to their native countries.…”
Section: Effects Of Selection and Acculturationmentioning
confidence: 99%
“…As a consequence, the application of the prevalence in the country of origin to overseas communities is likely to bias first generation indirect estimates of FGM/C occurrence (Mafukidze 2006;Kohnert 2007;Behrendt 2011). The selection effect also has a direct impact on the continuation of the practice on daughters born in emigration, but the phenomenon among second and subsequent generations should be analysed separately, according to a "mother-todaughter transmission" approach accounting for the impact of family and community network characteristics (Farina and Ortensi 2014;Hayford 2005).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The Italian region of Lombardy is chosen as a case study because direct estimates for women from selected countries of origin are available for the year y=2010 and provide us with a unique opportunity to compare direct and indirect estimates of prevalence. Direct estimates are taken from the Regional Survey on the Prevalence of Women at Risk of FGM/C (Farina 2010;Farina and Ortensi 2014;Table 5). …”
Section: Case Study: Estimating the Prevalence Of Women With Fgm/c Inmentioning
confidence: 99%
“…The methodology used in this analysis allowed us to assess whether normative influences as well as women's support for FGM/C are key to its continuation in Nigeria and revealed areas where the practice is prevalent ("hotspots") with associated risk factors. In Senegal, Burkina Faso, and Egypt, Farina and Ortensi (2014) found that FGM/C prevalence among daughters was higher for those whose mothers were cut. A study in Kenya (Achia 2014) found that a woman's FGM/C status was a key determinant of her support for the continuation of the practice.…”
Section: Discussionmentioning
confidence: 94%